Aplicação de espectrometria de massa com ionização paper spray em análises de cunho forense e no monitoramento e aceleração de reações quimicas - Camila Cristina Almeida de Paula (2018)
The present work employed the analytical technique denominated Paper Spray Mass Spectrometry (PS-MS) in two distinct themes of high current relevance: forensic analyses and monitoring and acceleration of chemical reactions. In forensics, the PS-MS technique was successfully applied in the identification and quantification of cocaine in drug street samples in the identification of the scam known in Brazil as "Boa noite, Cinderela" from analyses of spiked drinks. For the cocaine analyses, samples were prepared in the laboratory using different matrices (wheat flour, boric acid and sodium bicarbonate) in order to simulate the chemical composition of the seized materials. The results obtained (identification of cocaine in samples containing 0.01% to 5% of cocaine)were as conclusive as those obtained through the methodology normally employed in forensic laboratories (Scott colorimetric test associated with chromatographic analysis) requiring less time and inputs. To confirm the scam "Boa noite, Cinderela", different beverages (beer, vodka, soda and juice) were spiked with benzodiazepines, which could be identified and quantified (quantification of Diazepam only in beer) reliably, quickly and economically through of a simple sample pre-treatment (liquid-liquid extraction with low temperature partitioning) associated with PS-MS technique. For the monitoring of chemical reactions, the PS-MS technique was employed to monitor a model reversible system under conditions that alter its dynamic chemical equilibrium, the methylene blue redox system, established when a reducing agent (metallic zinc) is put into contact with an acid solution of this dye. The PS-MS technique was also used to monitor and accelerate chemical reactions between phthalic anhydrite and diamines for the formation of phthalimide derivatives, compounds of remarkable pharmacological interest, whose synthesison a bench scale may take hours. Both works obtained in situ results that provided structural information of possible products and reaction intermediates, as well as their respective reactional pathways. In addition, these last two works have another noble application: the development of didactic content to elaborate practical classesfor undergraduate students.